Effect of the Gall Wasp Leptocybe invasa on Hydraulic Architecture in Eucalyptus camaldulensis Plants - Tong, You-Gui; Ding, Xiao-Xi; Zhang, Kai-Cun; Yang, Xin; Huang, Wei (Frontiers in Plant Science, 2016)
The gall wasp, Leptocybe invasa (Hymenoptera; Eulophidae), is a devastating pest of eucalypt plantations in the Middle East, the Mediterranean basin, Africa, India, South-East Asia, and China. Heavy galling causes the leaves to warp and in extreme cases it may stunt the growth of the trees of Eucalyptus camaldulensis. However, the physiological mechanisms underlying how L. invasa inhibits the growth of plants of E. camaldulensis are unclear. Because the growth rate of plants is mainly dependent on photosynthesis that is largely correlated with hydraulic architecture, we speculate that galling of L. invasa depresses hydraulic conductance of stem and leaf. In the present study, we examined the effects of L. invasa galling on hydraulic architecture and photosynthetic parameters in E. camaldulensis plants. We found that galling of L. invasa significantly decreased stem hydraulic conductance (Kstem), midday leaf water potential (md), minor vein density (MVD), and stomatal density (SD). Furthermore, the stomatal conductance (gs), chlorophyll content, CO2 assimilation rate (An) and photosynthetic electron flow were reduced in infected plants. Therefore, the galling of L. invasa not only declined the water supply from stem to leaves, but also restricted water transport within leaf. As a result, galled plants of E. camaldulensis reduced leaf number, leaf area, SD and gs to balance water supply and transpirational demand. Furthermore, galled plants had lower leaf nitrogen content, leading to decreases in chlorophyll content, CO2 assimilation rate and photosynthetic electron flow. These results indicate that the change in hydraulic architecture is responsible for the inhibition of growth rate in galled plants.